0167 Sleep Quality is Both a Predictor and a Consequence of Neuroticism Longitudinally. (12th April 2019) - Li, Cheng; Ying Lau, Esther Yuet; Hui, C Harry; Lam, Jasmine; Cheung, Shu F; Cheung, Sing H
Abstract: Introduction: Poor sleep quality is a significant health issue which may be affected by individual characteristics like personality and can bring changes to personality over time as well. As found in a longitudinal study using secondary samples (Stephan et al., 2018), neuroticism (i.e. low emotional stability) at baseline is associated with poor sleep quality at follow up, and higher sleep difficulties at baseline is associated with less of a decrease in neuroticism over time in middle aged and older adults. However, sleep quality was not measured by a validated sleep measure and the follow-up was conducted only once, either four or ten years later. The present study aims to investigate the association between neuroticism and sleep quality using a validated sleep measure administered three times in a younger generation. Methods: 7186 individuals (mean age=24.86, SD=7.75, Range=18-77; 64.06% women) completed an online survey at three time points: The Pittsburgh Sleep Quality Index (PSQI) and the International Personality Inventory Pool (IPIP) at baseline (Wave 1), four years later (Wave 5), and five years later (Wave 6). Results: Cross-lagged analyses revealed that emotional stability prospectively predicts sleep quality both one year (βstand = -.168, p < 0.001) and four years later (βstand = -.128, p < 0.001); sleep quality predicts emotional stability prospectively four years later (βstand = -.070, p < 0.05) but not one year later (βstand =-.031, p > 0.05). Conclusion: Low emotional stability predicts poor sleep quality in the short run (one year) and the long run (four years), while poor sleep's effect on neuroticism is evident only in the long run in Chinese young adults. Our findings provide novel information on the long-term effects of sleep quality (which is a more transient variable) on neuroticism (which is a more enduring trait). The pervasiveness of prolonged poor sleep quality is underlined, and further investigations into the neuropsychosocial mechanisms of the bidirectional relationships are warranted. Support (If Any)